2014
DOI: 10.1557/jmr.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

Fracture transitions in iron: Strain rate and environmental effects

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The amount of plastic energy dissipation depends upon stress field interactions between the crack tip and the emitted dislocations based upon the applied stress tensor, r ij . This stress field problem can then be related to G IC through the applied strain rate, _ e. Considering the interdependence of plasticity and fracture, the dislocation activation parameters V*, s*, H 0 can be combined to describe the dislocation velocity, v, as done in Hintsala et al 204 to dictate the shielding of the crack tip by dislocations. The dislocation activation parameters will depend upon the temperature, T, and the presence of impurities.…”
Section: Future Nanomechanical Approaches To Brittleness Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of plastic energy dissipation depends upon stress field interactions between the crack tip and the emitted dislocations based upon the applied stress tensor, r ij . This stress field problem can then be related to G IC through the applied strain rate, _ e. Considering the interdependence of plasticity and fracture, the dislocation activation parameters V*, s*, H 0 can be combined to describe the dislocation velocity, v, as done in Hintsala et al 204 to dictate the shielding of the crack tip by dislocations. The dislocation activation parameters will depend upon the temperature, T, and the presence of impurities.…”
Section: Future Nanomechanical Approaches To Brittleness Transitionsmentioning
confidence: 99%
“…This requires understanding of how confining pressure, 205 radiation enhanced dislocation glide (REDG), 206 impurities, 207 state of stress, 208 and length scale 209 affect dislocation nucleation and mobility. The REDG effect 204 is important since most studies of length scale effects at submicron sizes are accomplished in either SEM or TEM. Maeda et al 206 observed from TEM experiments on SiC a roughly linear increase in dislocation velocities with increasing electron beam intensity, though the velocity depends on dislocation length and dislocation character.…”
Section: Future Nanomechanical Approaches To Brittleness Transitionsmentioning
confidence: 99%
“…One possibility that could include all the variables outlined in the previous section is an approach we had proposed previously [17,28] which included s*V*, similar to what has been used for thermally activated creep mechanisms: [29] …”
Section: Modelingmentioning
confidence: 99%
“…[16] It has become generally accepted that this allows dislocation shielding to provide an increase in the fracture toughness. [6,[17][18][19] However, an accurate model for predicting the DBT has not yet been achieved due to many complicating variables which require extensive data to evaluate. To give some sense of the problem, a number of variables known to affect dislocation nucleation and mobility in silicon are:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation